Optimizing Safe Dental Practice During the COVID-19 Pandemic: Recommendations Based on a Guide Developed for Dental Practices in China - Li, Li; Zeng, Mianyan; Chen, Xiao; Cai, Shuman; Xu, Cuixia; Xia, Wei; Jiang, Lijun; Zou, Xiaoyan; Chen, Pei; Rong, Mingdeng (Frontiers in Medicine, 2021)
The current global coronavirus disease 2019 (COVID-19) outbreak is still exerting severe global implications, and its development in various regions is complex and variable. The high risk of cross-infection poses a great challenge to the dental practice environment; it is therefore urgent to develop a set of pandemic prevention measures to ensure dental practice safety during the COVID-19 outbreak. Therefore, we combined the epidemiological characteristics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), public emergency measures for COVID-19, characteristics of dental practice, and relevant literature reports to develop a set of dynamic practice measures for dental practices in high, medium, and low-risk areas affected by COVID-19. This will help dental practices to achieve standard prevention, and ensure their safe and smooth operation during the pandemic. It is hoped that these measures will provide a reference basis for dental hospitals and dental clinics in their care and pandemic prevention work.